Altered expression of genes involved in ganglioside biosynthesis in substantia nigra neurons in Parkinson’s disease - Schneider, Jay S. (PLOS ONE, 2018)
Reduced expression of GM1 and other major brain gangliosides GD1a, GD1b and GT1b have been reported in Parkinson’s disease (PD) brain. Mechanisms underlying these changes are unclear but may be due to a deficit in the ganglioside biosynthetic process. The present study examined the extent to which deficits in gene expression of key biosynthetic enzymes involved in synthesis of GM1 and GD1b (B3galt4) and GD1a and GT1b (St3gal2) exist in neuromelanin-containing neurons in the PD substantia nigra (SN). In situ hybridization histochemistry was used to examine gene expression of B3GALT4 and ST3GAL2 in neuromelanin-containing neurons in the SN in 8 normal controls (61–92 yrs.) and 7 PD subjects (77–95 yrs). There was a significant decrease in both B3GALT4 and ST3GAL2 gene expression in residual neuromelanin-containing cells in the SN of PD patients compared to age-matched neurologically normal controls. These changes appeared to be cell-type specific as abundant B3GALT4 and ST3GAL2 gene expression was observed in non-neuromelanin containing neurons located outside of the SN in the PD brain. These data show that residual neuromelanin-containing neurons in the PD SN have decreased expression of the ganglioside biosynthetic genes B3GALT4 and ST3GAL2, consistent with previous reports of decreased levels of gangliosides GM1, GD1a, GD1b and GT1b in the PD SN. These changes may increase the vulnerability of these neurons to degeneration in response to a variety of potential stressors.